2001
DOI: 10.1007/s004230100245
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of oral ofloxacin for single-dose perioperative prophylaxis in general surgery – a controlled randomized clinical study

Abstract: The data demonstrate that single-dose oral ofloxacin is at least as effective as a standard intravenous prophylaxis in patients with colonic or pancreatic resection. It offers significant advantages regarding costs and ease of administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
5
0
2
Order By: Relevance
“…Most clinical experience has been gained with ciprofloxacin and ofloxacin (28). Oral administration of quinolones was efficacious in surgical prophylaxis, even after a single dose (6,39), and also facilitates prolonged therapy. In in vitro studies, Staphylococcus aureus penetrates and survives in bone cells, i.e., osteoblasts (25); therefore, quinolones, which penetrate intracellularly, might be of advantage.…”
mentioning
confidence: 99%
“…Most clinical experience has been gained with ciprofloxacin and ofloxacin (28). Oral administration of quinolones was efficacious in surgical prophylaxis, even after a single dose (6,39), and also facilitates prolonged therapy. In in vitro studies, Staphylococcus aureus penetrates and survives in bone cells, i.e., osteoblasts (25); therefore, quinolones, which penetrate intracellularly, might be of advantage.…”
mentioning
confidence: 99%
“…Our study showed that levofloxacin distributes into the ECF of rat pancreatic tissue (AUC pancreas /AUC blood , 0.97 ± 0.02) with IV and (AUC pancreas /AUC blood , 0.96 ± 0.03) with PO. The degree of tissue penetration with levofloxacin correlates well with other quinolones such as moxifloxacin,[21] ciprofloxacin,[22] ofloxacin[23] and gatifloxacin [24]. These facts suggest that equal bioavailability is achieved for levofloxacin with intravenous and oral formulations.…”
Section: Discussionmentioning
confidence: 81%
“…Ayrıca, oral antibiyotiğin emilimini olumsuz etkileyebilecek birçok neden olabileceğinden, oral antibiyotik profilaksisi cerrahi alan infeksiyonlarını engelleme adına tercih edilen bir uygulama değildir. Buna karşın, son yıllarda yapılan bazı kontrollü çalışmalar gastrointestinal emilimi iyi olan antibiyotiklerle yapılan oral profilaksinin parenteral antibiyotikler kadar etkin olduğunu göstermiştir (26,27). Henüz rutin öneri düzeyinde olmamakla birlikte, ilerleyen yıllarda oral antimikrobiyal profilaksi cerrahide tercih edilebilecektir.…”
Section: Uygulama Yoluunclassified